Syndrome Evaluation System for Simultaneous Detection of Pathogens Causing Acute Encephalitic Syndrome in India, Part-2: Validation Using Well Characterized Clinical Samples - Govekar, Sunil R.; Lakshman, Latha P.; Reddy, Vijayalakshmi; Mani, Reeta S.; Mahadevan, Anita; Susarla, Shankar K.; Desai, Anita; Banda, Ravi Kumar Venkata; Vasanthapuram, Ravi (Frontiers in Neurology, 2019)
Diagnosis of the aetiological agent in case of acute encephalitic syndrome (AES) continues to pose a challenge in clinical practice as a variety of pathogens are known to cause AES. Here, we report the validation of a Syndrome Evaluation System (SES) developed for simultaneous detection of multiple AES pathogens using a well characterized set of Cerebrospinal fluid (CSF) samples. The validation of the SES was carried out in two phases. In the first phase, the SES was validated using 51 CSF samples obtained from autopsy proven cases and 50 samples obtained from apparently healthy individuals undergoing spinal anaesthesia for minor surgeries served as ‘controls’. The SES detected etilogical agent in 48/51 (94.11 %) samples obtained from autopsy proven AES cases while all the 50 CSF samples obtained from ‘controls’ were negative. In the second phase, the SES was validated using well characterised CSF samples obtained from AES patients fulfilling the WHO case definition of AES (Group I; n=207) and samples that were collected from patients with non-infectious neurological disorder(Group II; n=90). All the samples were tested using multiple conventional/serological assays and categorised into various groups. Amongst the AES cases fulfilling WHO case definition, the SES detected AES pathogens in 160/207 (77.29%) cases while conventional serological/molecular assays were able to detect AES pathogens only in 77/207 (37.1%) of cases. Further, in 12/83 CSF samples that were positive by SES and negative by conventional serological/molecular tests, the results were additionally confirmed by sequencing the PCR products to rule out non-specific amplification in the SES. In patients with non-infectious neurological disorders the SES detected latent viruses 12/90 CSF samples. These results indicate that the SES, apart being a rapid, sensitive, specific and cost-effective method provides the major advantage of simultaneous detection of multiple pathogens using as single specimen of CSF.